2020
DOI: 10.1080/13691457.2020.1760796
|View full text |Cite
|
Sign up to set email alerts
|

Into the swampy lowlands. Evaluating family group conferences

Abstract: A recent debate in the UK on the merits of randomised controlled trials in evaluating Family Group Conferencing is a reason to bring this debate to a wider audience than the UK. Other countries are also struggling with accountability and the desire to know what works in the light of public spending. This paper explores, debunks and rethinks ways of evaluating FGCs and how it is connected to our desire to predict and control future circumstances. For the latter insights of the Dutch philosopher Kunneman are use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Do patients and caregivers fear a loss of privacy or independence when seeking help from friends or family? Supporting people in overcoming feelings of shame can be helpful (Schout, 2020), but only after couples have indicated that they actually want to involve others but have never learned how to do that. If, by contrast, people indicate that they do not want to involve those in their social network, this should be respected.…”
Section: Discussionmentioning
confidence: 99%
“…Do patients and caregivers fear a loss of privacy or independence when seeking help from friends or family? Supporting people in overcoming feelings of shame can be helpful (Schout, 2020), but only after couples have indicated that they actually want to involve others but have never learned how to do that. If, by contrast, people indicate that they do not want to involve those in their social network, this should be respected.…”
Section: Discussionmentioning
confidence: 99%
“…The value of the taken for granted application of RCT as the golden design in the evaluation of FGC is questioned by de Jong et al (48), de Jong and Schout (71), and Schout (72). They suggest that the complexity of researching FGC requires a highly nuanced approach, which qualitative research methodology would be more suitable for, while acknowledging that a qualitative methodology depends on the interpretative perspective of the researchers.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…The mixed research outcomes have spurred a debate on what should be considered the most appropriate research methodology to examine the FGC model. Randomized‐research designs are criticized for failing to consider the complex contextual reality of families and merely providing partial insights into the efficacy of the FGC model (Creemers et al, 2017; de Jong & Schout, 2018; Schout, 2022). In light of this debate, scholars advocate for future research to embrace this complexity rather than simplifying it and propose that analysing each conference as a unique case is essential to comprehend the multidimensional nature of FGC (de Jong & Schout, 2018; Schout, 2022).…”
Section: Introductionmentioning
confidence: 99%